Assessment of Primary Sources of Stress Among Staff Nurses in Sir Gangaram Hospital, Lahore - Maqsood, Tahira; Sajid, Ammara; Ashraf, Amina; Noor, Manaza; Mushtaq, Khudija; Saeeda, Khawer (Biological and Clinical Sciences Research Journal, 2025)
Nursing is globally recognised as a highly demanding profession characterised by emotional labour, hierarchical pressures, understaffing, and heavy workloads. In Pakistan, these challenges are intensified by limited healthcare resources, political influence over workplace decisions, and inadequate administrative support, all of which contribute substantially to occupational stress among nurses. Objective: To assess the primary sources of occupational stress among staff nurses working at Sir Ganga Ram Hospital, Lahore, and determine the perceived prevalence and burden of stress in their clinical practice. Methods: A descriptive cross-sectional study was conducted at Sir Ganga Ram Hospital, Lahore, over six months from February to July 2025. A convenience sample of 384 registered nurses with at least 1 year of experience was surveyed using a validated, structured questionnaire comprising demographic information, a 17-item Likert-based stress scale, and seven dichotomous organisational stress items. Instrument reliability was established through pilot testing, and Cronbach’s alpha exceeded 0.70. Data were analysed in SPSS using descriptive statistics. Results: The majority of participants were female (95.6%) and married (63.5%). Emotional strain was prevalent: 53.6% sometimes felt upset by unexpected events, and 31.7% often or very often felt nervous or stressed. Nearly 36.2% lacked confidence in handling problems, and 43% felt things were not going well at least sometimes. Workload stress was notable: 31.8% reported a lack of time to complete tasks, and more than half reported persistent staffing shortages. Interpersonal factors, including criticism from physicians, weak team communication, and emotional exhaustion, were frequent. Organisational stressors were prominent, with 60.2% citing political influence and 61.2% attributing stress to management practices. Overall, 81.8% perceived nursing as a stressful profession, and 51% personally reported feeling stressed during duty. Conclusion: Nurses at Sir Ganga Ram Hospital experience substantial occupational stress arising from workload burdens, interpersonal conflicts, emotional exhaustion, and organisational limitations. System-level interventions addressing staffing, leadership support, communication, and workload management are required to mitigate stress and enhance nurse wellbeing.